Использование podcasts при обучении иностранным языкам - Исмагулова, Г.К.; Руденко, А. (My University, 2016)
This article discusses the new format for distributing audio and video content over the Internet. This kind of social service lets you listen, browse, create and distribute audio and video recordings. The aim of this is to optimize the implementation of the methodology and the efficiency of foreign language lessons.
Keywords: FL- teaching methodology; Podcast; online resources.